The Impact of Exercise on Motor Recovery after Long Nerve Grafting—Experimental Rat Study - Camuzard, Olivier; Lu, Johnny Chuieng-Yi; Abbadi, Sam El; Chang, Tommy Nai-Jen; Chuang, David Chwei-Chin (Journal of Reconstructive Microsurgery, 2023)
Background Long nerve grafting often results in unsatisfactory functional outcomes. In this study we aim to investigate the effect of swimming exercise on nerve regeneration and functional outcomes after long nerve grafting.Methods A reversed long nerve graft was interposed between C6 and the musculocutaneous nerve in 40 rats. The rats were divided into four groups with 10 in each based on different postoperative swimming regimes for rehabilitation: group A, continuous exercise; group B, early exercise; group C, late exercise; and group D, no exercise (control group). A grooming test was assessed at 4, 8, 12, and 16 weeks postoperatively. Biceps muscle compound action potential (MCAP), muscle tetanic contraction force (MTCF), and muscle weights were assessed after 16 weeks. Histomorphometric analyses of the musculocutaneous nerves were performed to examine nerve regeneration.Results The grooming test showed all groups except group D demonstrated a trend of progressive improvement over the whole course of 16 weeks. Biceps MCAP, MTCF, and muscle weights all showed significant better results in the exercise group in comparison to the group D at 16 weeks, which is especially true in groups A and B. Nerve analysis at 16 weeks, however, showed no significant differences between the exercise groups and the control group.Conclusions Swimming after long nerve grafting can significantly improve muscle functional behavior and volume. The effect is less evident on nerve regeneration. Continuous exercise and early exercise after surgery show more optimal outcomes than late or no exercise. Having a good habit with exercise in the early period is thought as the main reason. Further studies are needed to determine the optimal exercise regimen.
Keywords: long nerve grafts; swimming; motor